2013
DOI: 10.3844/ajessp.2013.388.397
|View full text |Cite
|
Sign up to set email alerts
|

Monstrous Hazards Produced by High Radioactivity Levels Around Assiut Thermal Power Plant

Abstract: The natural radioactivity level of heavy oil, ash and soil samples around Assiut Thermal Power Plant (ATPP) in Egypt was determined using gamma ray spectrometry. The average concentrations of 226 Ra, 232 Th and 40 K in fly ash were found to be 2307±143, 1281±80 and 1218±129 Bq kg −1 , respectively, while the corresponding values in soil samples were 2670±107, 1401±78 and 1495±100 Bq kg −1 , respectively. These are extremely high and higher by several orders of magnitude than the worldwide population-weighted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The annual effective dose rate received by the local residents outdoor due to natural radioactivity in soil ranges from 0.05 to 15.6 mSv yr-1 with an average of 2.2 mSv yr -1 . The dose rate was higher than that of the studied thermal power plant and the global average for outdoor exposure [20].…”
Section: Fig (4): Total Effective Doses Equivalent Via Ingestion Pathwaymentioning
confidence: 60%
“…The annual effective dose rate received by the local residents outdoor due to natural radioactivity in soil ranges from 0.05 to 15.6 mSv yr-1 with an average of 2.2 mSv yr -1 . The dose rate was higher than that of the studied thermal power plant and the global average for outdoor exposure [20].…”
Section: Fig (4): Total Effective Doses Equivalent Via Ingestion Pathwaymentioning
confidence: 60%
“…In previous research it was detemined that activity concentration of radionuclides in the mosses coud be used as effective indicator of radioactivity pollution in different polluted zones (El-Gamal et al, 2013;Minkina et al, 2014). In research El-Gamal et al (2013) it was shown that mosses are used for urboecomonitoring for definition of high radioactivity levels around assiut thermal power plants. In investigation of Minkina et al (2014) describes additional influence of of heavy metal attendant anion on adsorbtion of polluted material by plants system.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research it was detemined that activity concentration of radionuclides in the mosses coud be used as effective indicator of radioactivity pollution in different polluted zones (El-Gamal et al, 2013;Minkina et al, 2014). In research El-Gamal et al (2013) it was shown that mosses are used for urboecomonitoring for definition of high radioactivity levels around assiut thermal power plants.…”
Section: Resultsmentioning
confidence: 99%
“…In research El-Gamal et al (2013) it was shown that mosses are used for urboecomonitoring for definition of high radioactivity levels around assiut thermal power plants. In investigation of Minkina et al (2014) describes additional influence of of heavy metal attendant anion on adsorbtion of polluted material by plants system.…”
Section: Resultsmentioning
confidence: 99%